Mixing effects on light exposure in a large‐lake epilimnion: A preliminary dual‐dye study. (19th May 2016) - Minor, Elizabeth C.; Austin, Jay A.; Sun, Luni; Gauer, Lance; Zimmerman, Richard C.; Mopper, Kenneth
Abstract: Light plays a critically important role in driving photo‐ and biogeochemistry of aquatic systems, and our ability to measure and model submarine light fields is fairly sophisticated. However, previous approaches have relied almost entirely upon Eulerian rather than Lagrangian measurements. Such approaches can provide good estimates of the instantaneous light field but do not necessarily reflect the doses of light experienced by particles and chemical species passively transported by physical processes within a lake or ocean surface‐layer. Here, a novel dual‐dye approach, used as a Lagrangian light dosimeter, was applied in Lake Superior's surface mixed layer to determine the importance of mixing in affecting the light dose experienced by particles passively mixed within is this layer. Two fluorescent dyes were deployed in the water column in a known ratio; one of the dyes (fluorescein) was sensitive to light exposure and one (rhodamine WT) was relatively photostable. The photochemistry of the dyes (i.e., the quantum yield of fluorescence bleaching at different wavelengths) and the role of matrix effects on dye response in a natural water system were explored with laboratory experiments. Decay equations for fluorescein and rhodamine WT fluorescence were determined from controlled irradiations of dye solutions with natural sunlight. The mixed‐layer light dose (from 460 nm to 510 nm) was then traced for two dye deployments in Lake Superior. The results show the importance of vertical mixing on the light dose within Lake Superior's surface layer on time scales of hours.